(Un)Making Chorography: Ecstatic Dance Along California’s Coast - Dickason, Kathryn (Numen, 2025)
Contemporary ecstatic dance began in Hawaii in 2001 and has since become a global phenomenon. It involves improvised movements and a live DJ, and does not have any direct religious affiliation. Drawing from fieldwork in California and the disciplines of religious studies and dance studies, this study investigates how spontaneous bodily movements create sacred space. The first section theorizes ecstatic dance through the lens of “chorography,” a neologism coined by Byzantinist Nicoletta Isar that encapsulates the dynamic, sacralizing interplay between space and movement. The second section addresses some potentially unsavory and threatening aspects of ecstatic dance – namely cultural appropriation and lapses in consent – that destabilize chorographic sacrality. In sum, this study shows how religiosity can emerge from otherwise secular contexts while revealing the fragility of the sacred.